Comparing Modeled and Experimental Accelerated Corrosion Tests on Steel. Issue 9 (1st January 2017) - Steen, N. Van den; Simillion, H.; Thierry, D.; Terryn, H.; Deconinck, J.
Abstract : Four different accelerated corrosion tests on steel are simulated with a Dynamic Electrolyte Film Corrosion model. Based on the time dependent temperature and humidity, combined with the presence of hygroscopic salts, a time dependent electrolyte thickness is calculated. At every timestep, the modeled film thickness dictates the corrosion current. Focussing on the thickness predictions, an elementary corrosion model is adopted to enable the corrosion depth estimations. The trends of the simulated corrosion depths are compared with experimental data obtained with an electrical resistance corrosion sensing system, demonstrating the importance of the electrolyte thickness and composition for a thorough understanding and modeling of atmospheric corrosion on steel.